Comparative Pharmacokinetic Profiles of Puerarin in Rat Plasma by UHPLC-MS/MS after Oral Administration of Pueraria lobata Extract and Pure Puerarin - Guozhe Zhang; Jianwei Ji; Mingzhong Sun; Yuqiao Ji; Hongjian Ji (Journal of Analytical Methods in Chemistry)
Puerarin is the main biologically active isoflavone in Pueraria lobata and has a wide range of biological activities. However, due to its poor water solubility and low oral bioavailability, its clinical applications are restricted. Compared with puerarin, the Pueraria lobata extract (PLE) has better water solubility, lower toxicity, and less side effects. In this study, the pharmacokinetics of orally administered puerarin (100 mg/kg) and PLE (763 mg/kg, equivalent to 100.0 mg/kg of puerarin) to rats was investigated by the UHPLC-MS/MS method. Results showed that when the rats were administered PLE, the area under the concentration-time curve from zero to infinity (AUC0-inf) dramatically increased from 219.83 ± 64.37 μg h/L to 462.62 ± 51.74 μg h/L (p<0.01). The elimination half-time (t1/2) also increased from 1.60 ± 0.38 h to 12.04 ± 5.10 h (p<0.01). The maximum concentration (Cmax) of puerarin decreased from 101.64 ± 41.82 ng/mL to 48.64 ± 21.47 ng/mL (p<0.01), and time to reach the maximum plasma concentration (Tmax) of puerarin decreased from 1.46 ± 1.08 h to 0.54 ± 0.30 h (p<0.01). Results indicated that the pharmacokinetics of puerarin in Pueraria lobata may be dramatically different from pure puerarin in the plasma of rat, and oral bioavailability of puerarin may be increased when PLE was administrated to rats.